The Principal's Strategy in Developing Islamic Boarding School-Based Educational Institutions - Muzakki, Ahmad; Sugiono, Sugiono (International Journal of Instructional Technology, 2024)
This study aims to investigate the principal's strategy in developing pesantren-based educational institutions, with a focus on MTs Nurul Qur'an Patokan-Kraksaan. In the dynamics of modern education, the role of school principals is very important in directing the development of educational institutions, especially in the pesantren environment. However, in-depth research on the strategies implemented by school principals in the context of pesantren education is still limited. A descriptive qualitative approach is used, by collecting data through interviews, observations, and documentation. Data analysis was carried out using data triangulation to obtain a comprehensive understanding of the principal's strategy in developing Islamic boarding schools. The findings of the study show that the characteristics of school principals, such as discipline, clear vision, democratic approach, and ability to manage resources, play a key role in the development of Islamic boarding school educational institutions. School principals who meet these characteristics are able to lead effectively, strengthen the identity of pesantren through the integration of religious teachings with modern curriculum, and utilize information technology to improve the efficiency and effectiveness of learning. In addition, resource management and the development of partnerships with local communities are also important aspects that school principals strive for to ensure the sustainability and growth of Islamic boarding school educational institutions.